Finite Element Analysis of the Stress and Deformation in Bone Caused by CFR-PEEK, Titanium, and Zirconia Ceramic Implants - Ahmad Saib Jameel; Amiya Ranjan Sahoo; Viraj Kharkar; Harjit Singh Kalsi; Akanksha Singh; Vaibhav T. Chougule; Sharmila Behera (Wolters Kluwer Medknow Publications, 2024)
Introduction: Glass or carbon fiber-reinforced polyetheretherketone (CFR-PEEK) composites and zirconia ceramic have been offered as more modern implant biomaterials. Objectives: This study examined the effects of zirconia ceramic implants, titanium, and CFR-PEEK on bone stress and deformation. Materials and Methods: A geometric model of a mandibular molar replaced with an implant-supported crown was created for this in vitro finite element analysis investigation. The dimensions of the implant employed in the study are 11.0 mm in length and 4.5 mm in diameter. Using finite element analysis, three implant assemblies composed of zirconium, titanium, and CFR-PEEK were produced. 150 N loads were applied both vertically and obliquely on the long axis of the implant. The von-Mises stresses and deformation were compared using ANSYS Workbench 18.0 and finite element software, with a significance threshold of P < 0.05. Results: All three implant assemblies-zirconia, titanium, and CFR-PEEK-showed comparable stresses and deformation in bone with no appreciable variations. Conclusion: Zirconia and PEEK reinforced with carbon fibers (CFR-PEEK) have been found to be viable replacements for titanium in implant biomaterials.